2020
DOI: 10.1126/sciimmunol.aba1896
|View full text |Cite
|
Sign up to set email alerts
|

Absence of MHC class II on cDC1 dendritic cells triggers fatal autoimmunity to a cross-presented self-antigen

Abstract: Conventional dendritic cells expressing the XCR1 chemokine receptor (cDC1s) excel at cross-presentation. Here, we developed and used a mouse model in which a Cre recombinase is expressed under the control of the Xcr1 gene while preserving XCR1 expression. We used it to generate mice with conditional deletion of MHC class II (MHCII) molecules on cDC1s. By preventing cDC1s to receive suppressive regulatory T cell inputs via MHCII-restricted interactions, the objective of the present study was to gauge whether MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 52 publications
6
55
0
Order By: Relevance
“…Xcr1-IRES-iCre-2A-mTFP1 gene-targeted mice (also known B6-Xcr1tm2Ciphe mice and called XCR1.cre mice here) mice permit to specifically delete floxed gene in cDC1. 69 Batf3 KO and Het (B6.129S(C)-Batf3 tm1Kmm /J), CD11c-IFNAR KO ((B6.Cg-Tg(Itgax-cre)1-1Reiz/J 70 crossed to IFNAR floxed mice (obtained from U. Kalinke 47 )), XCR1-IFNAR KO (XCR1.cre crossed to IFNAR floxed mice) and huCD207-DTA 42 mice were bred and maintained in the Clinical Research Center at Lund University. β8 integrinreporter mice were generated on a C57Bl/6 background by expression of an internal ribosomal entry site-fluorescent tandem dimer (td)-Tomato cassette (IRES-Td-Tomato) immediately following the stop codon in exon 14 of Itgb8 (Fig.…”
Section: Micementioning
confidence: 99%
“…Xcr1-IRES-iCre-2A-mTFP1 gene-targeted mice (also known B6-Xcr1tm2Ciphe mice and called XCR1.cre mice here) mice permit to specifically delete floxed gene in cDC1. 69 Batf3 KO and Het (B6.129S(C)-Batf3 tm1Kmm /J), CD11c-IFNAR KO ((B6.Cg-Tg(Itgax-cre)1-1Reiz/J 70 crossed to IFNAR floxed mice (obtained from U. Kalinke 47 )), XCR1-IFNAR KO (XCR1.cre crossed to IFNAR floxed mice) and huCD207-DTA 42 mice were bred and maintained in the Clinical Research Center at Lund University. β8 integrinreporter mice were generated on a C57Bl/6 background by expression of an internal ribosomal entry site-fluorescent tandem dimer (td)-Tomato cassette (IRES-Td-Tomato) immediately following the stop codon in exon 14 of Itgb8 (Fig.…”
Section: Micementioning
confidence: 99%
“…To this end, a floxed transcriptional termination cassette was inserted into the coding sequence of the TLR3 gene (TLR3 OFF ), abolishing TLR3 expression. Expression of TLR3 by cDC1s could then be restored in cDC1.TLR3 ON mice, in which the TLR3 stop codon was deleted using XCR1-driven cre recombinase (XCR1.cre [27]) ( Fig. 2B and Supporting information Fig.…”
Section: Cell-intrinsic Tlr3-sensing Is Dispensable For DC Migrationmentioning
confidence: 99%
“…Both male and female mice were used between 8 and 16 weeks of age as no obvious age differences were detected. CD11c.cre mice (B6.Cg-Tg(Itgax-cre)1-1Reiz/J [44]) allow floxed gene deletion in CD11c-expressing cells, huCD207.cre mice drive floxed gene deletion in Langerhans cells and intesti-nal cDC2 [37], XCR1.cre mice permit to specifically delete floxed genes in cDC1 [27], villin.cre (B6.Cg-Tg(Vil-cre)997Gum/J) mice excise floxed genes in intestinal epithelial cells [45], and Rosa26-STOP-YFP mice allow tracking of cre specificity (B6.129 × 1-Gt(ROSA)26Sor tm1(EYFP)Cos /J). We used "switch-on" mutants carrying a floxed stop cassette in the endogenous locus prior to the gene of interest, allowing for re-expression of the targeted gene in the presence of cre for MyD88 [46], TLR3 and TRIF (unpublished, manuscript in preparation) (both generated at TU Munich, Germany).…”
Section: Micementioning
confidence: 99%
“…Another mechanism by which Tregs may contribute to peripheral tolerance induction is through conditioning of DCs. A recent compelling study found that conditional MHC Class II ablation from cross-presenting cDC1s disrupted CD8 + T cell peripheral tolerance, presumably due to impaired interactions between Tregs and cDC1s (90). These effects are likely due to the large range of direct effects that Tregs have on DC immunogenicity (82), in addition to enabling Treg recruitment to adjacent self-reactive CD8 + T cells for proximity-dependent IL-2 quenching.…”
Section: Cell Extrinsic Factors That Regulate Peripheral Tolerancementioning
confidence: 99%